An Extremely Elongated Cloud Over Arsia Mons Volcano on Mars: 2. Mesoscale Modeling. Issue 10 (18th October 2022) - Hernández‐Bernal, J.; Spiga, A.; Sánchez‐Lavega, A.; del Río‐Gaztelurrutia, T.; Forget, F.; Millour, E.
Abstract: In a previous work (Hernández‐Bernal et al., 2021, https://doi.org/10.1029/2020je006517 ) we performed an observational analysis of the Arsia Mons Elongated Cloud (AMEC), which stands out due to its impressive size and shape, quick dynamics, and the fact that it happens during the Martian dusty season. Observations show that its morphology can be split in a head, on the western slope of the volcano of around 120 km in diameter; and a tail, that expands to the west reaching more than 1, 000 km in length, making the AMEC the longest orographic cloud observed so far in the solar system. In this work we run the Laboratoire de Météorologie Dynamique Mesoscale Model to gain insight into the physics of the AMEC. We note that it is coincident in terms of local time and seasonality with the fastest winds on the summit of Arsia Mons. A downslope windstorm on the western slope is followed by a hydraulic‐like jump triggering a strong vertical updraft that propagates upwards in the atmosphere, causing a drop in temperatures of down to 30 K at 40–50 km in altitude, spatially and temporarily coincident with the observed head of the AMEC. However the model does not reproduce the microphysics of this cloud: the optical depth is too low and the expansion of the tail does not happen in the model. The observed diurnal cycle is correctly captured by the model for the head of the cloud. This work raises new questions that will guide future observations of the AMEC. Plain Language Summary: This is the second paper of our research on the Arsia Mons Elongated Cloud (AMEC), which is a visually impressive cloud on Mars. It appears on the western flank of the Arsia Mons volcano during a specific season right at sunrise. For 3 hr it grows, developing a thin elongated tail that has been observed to be as long as 1, 800 km. In our previous work we described available observations. In this work we run a high resolution atmospheric model that captures the effect of the Arsia Mons volcano on the atmosphere. This model shows that due to the presence of the volcano and its effect on the wind, air is forced upwards next to the volcano, leading to a drop in temperatures of 30°C, which causes the formation of the cloud under extreme conditions of humidity. This is a success of the model that provides a new understanding of this outstanding cloud, however, the accurate physics behind the extreme expansion of the AMEC are not fully understood yet. This work solves some questions and raises many new ones, which will be an aid in the planning of new observations. Key Points: We performed mesoscale model dynamic simulations of the Arsia Mons Elongated Cloud observed in the Martian southern solstice Topography‐induced circulation causes temperatures to drop by about 30 K at the observed origin location and local time of the cloud The cloud tail is much more elongated in the observations than in the model, which challenges our understanding of winds and microphysics